Use of complex supplements and light-differential effects for micropropagation of Hadrolaelia purpurata (= Laelia purpurata) and Encyclia randii orchids - doi: 10.4025/actasciagron.v34i4.12333 - Gonçalves, Letícia Menezes (2012)
In the current study, complex (coconut water and ripe-banana pulp) and specific (micronutrients, peptone and activated charcoal) supplements were added to Knudson-C medium (KC) medium to stimulate the in vitro propagation of Hadrolaelia purpurata (=Laelia purpurata) and Encyclia randii orchid species. The highest number of H. purpurata seedlings occurred in KC medium containing 90 g L-1 banana pulp maintained with 24-hour illumination. Positive effects of the banana pulp addition in KC medium were reported for the formation of seedlings and leaves from E. randii seeds. The seedling number from seeds of E. randii maintained with continuous illumination was also high in KC medium containing coconut water. Positive effects due to the addition of peptone were reported only in the case of seedling formation from E. randii seeds maintained under continuous illumination. The highest number of H. purpurata seedlings and leaves of E. randii occurred in cultures maintained in continuous illumination. The successful asymbiotic germination of the three-year-old seeds of two Brazilian native species from different regions at reduced costs offers an opportunity for the use of the techniques in commercial nurseries and for ex situ conservation of the native and explored orchid species.